Coronavirus pandemic: yesterday, today, tomorrow of the Russian economy - O. M. Makhalina; V. N. Makhalin; A. B. Yaroshchuk (Вестник университета, 2022)
The article analyzes the economic results of the crisis year 2020, identifies the factors that had a negative impact on the results of the year, examines the dynamics of macroeconomic indicators, determines the impact of various industries on GDP. The results of the analysis of citizens’ incomes for 2020, the dynamics of changes in the number of unemployed and the number of Russian citizens with incomes below the established subsistence level are presented. Restrictive measures related to the pandemic and the results of their effect on the socio-economic development of Russia and some foreign countries are considered, the main anti-crisis measures are listed. The content and objectives of the “National Action Plan”, which is aimed at restoring the Russian economy, are briefly formulated. In conclusion, the main challenges and risks in the implementation of the “National Action Plan” are formulated, which provides both an increase in employment, an increase in citizens’ incomes, the restoration of economic growth and a fundamental changes in the structure of the economy.